Improving the SME’s Value Proposition’s Delivery: The Case of PT Abdi Property Indonesia - Brigitta Lydia Suwanto; Dony Abdul Chalid (ABDIMAS: Jurnal Pengabdian Masyarakat, 2023)
This paper aims to analyze how the development of a company’s value proposition can be improved. The method used is qualitative research to see how companies improve the way they deliver value propositions. The delivery of the company's value propositions has been improved through several stages, from the value proposition canvas and benefits map to message frameworks. Delivering the value of solutions and offers offered and provided by the company to its customers, namely through internal communication media, websites, Mamikos, WhatsApp, and Instagram. The research results are expected to help develop the company’s ability to deliver its value proposition, which can increase the company's occupancy and income.